Anatomic characteristics and novel transplantation model of the canine uterus - Xuan-Hai Do; Thanh-Hai Tong; Trung-Chuc Nguyen; Tuan-Anh Ngo; Minh-Trang Thi Tran (Korean Journal of Transplantation, 2023)
Background : In Vietnam, the rate of absolute uterine factor infertility is increasing, but no study has been published on uterine transplantation. The present study was designed to comprehensively observe the canine uterine anatomy and to examine the possibility of using a living canine donor for uterine transplantation training and further research. Methods : Ten female Vietnamese mixed-breed dogs were sacrificed for anatomical research, and 15 additional pairs were used to evaluate the novel uterine transplant model. Results : The anatomic features of the canine uterus differed considerably from those of the human uterus, with the uterine vessels originating from branches of the pudendal vessels (also known as the vaginal vessels). The uterine vascular pedicle had a small diameter (1 to 1.5 mm for arteries and 1.2 to 2.0 mm for veins) and required manipulation under a microscope. To perform uterine transplantation, the donor specimen’s artery and vein lengths were successfully reconstructed by anastomosis between both sides of the vasculature using autologous Y-shaped subcutaneous veins. The living-donor uterine transplantation model constructed in this study was feasible, with the transplanted uterus surviving in 86.7% of cases (13/15). Conclusions: Uterine transplantation was successfully performed in a Vietnamese canine living donor model. This model could be helpful in uterine transplantation training and improve the transplantation success rate in humans.